Corporate Governance and Implications for Minority Shareholders in Turkey - Burcin Yurtoglu (Turkish Economic Association, 2003)
This paper reports on the ownership and control structures of publicly listed firms in Turkey using data from 2001. While holding companies and non-financial firms are the most frequent owners at the direct level, families ultimately own more than 80 percent of all publicly listed firms in Turkey. Pyramids and dual class shares are common devices that families use to separate their cash-flow rights from control rights. We also show that such deviations result in significantly lower market to book ratios suggesting large agency costs because of the conflict of interests between controlling families and minority shareholders.
Keywords: G31; G32; O16; 330; Ownership Structure; Corporate Governance; Business Groups; Family Ownership; Turkey